2014
DOI: 10.1093/ajh/hpu212
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gender and Menopausal Status on Relationships Between Biological Aging, as Indexed by Telomere Length, and Aortic Stiffness

Abstract: Gender and premenopausal status do not affect age-related decreases in T/S and associations between T/S and PWV. In participants of African descent in whom telomere length did not differ by gender, the impact of gender prior to menopause on CVD is unlikely to be attributed to differences in the effect of biological aging on aortic stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
2
11
1
Order By: Relevance
“…This is in agreement with the results of recent publication by Raymond and colleagues [33]. Central hemodynamic parameters—specifically rAI, central BP, and PP—could change by various conditions such as treatment, pulse rate, or vascular stiffness at the time of measurements.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with the results of recent publication by Raymond and colleagues [33]. Central hemodynamic parameters—specifically rAI, central BP, and PP—could change by various conditions such as treatment, pulse rate, or vascular stiffness at the time of measurements.…”
Section: Discussionsupporting
confidence: 93%
“…In a study of persons of African descent, significant relationship between LTL and aortic stiffness was observed in both genders, but was also seen in premenopausal women. [33]. It is possible that telomere length in white blood cells may change in parallel with that of vascular cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we did not include systolic blood pressure (SBP) in our regression analyses to avoid introducing collinearity in the models. Similarly, we did not include measures of dietary or exercise, which both have been found to have beneficial effects on cognition 35 , as recent studies have reported a significant impact of these non-drug interventions on arterial stiffness by several mechanisms 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Other measures of body condition that were not measured, however, could still act as potential confounding factors. Further, as some of our qPCR reaction efficiencies were slightly lower than other studies that used qPCR to quantify TL [85,86], the results should be taken with caution.…”
Section: Discussionmentioning
confidence: 70%